2014
DOI: 10.1080/08856257.2014.882058
|View full text |Cite
|
Sign up to set email alerts
|

From thinking to practice: school staff views on disability inclusion in Turkey

Abstract: This paper presents outcomes of a qualitative interview study conducted in four Turkish primary schools that had been identified by the Ministry of Education as engaging in the inclusion of disabled students. The main purpose of the study was to examine school staff views on inclusion in their schools. Data were collected through semi-structured interviews with four class teachers and four school counsellors. Findings from the thematic analysis of the interview transcripts suggested that: (a) school staff held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…This finding demonstrates that the academic staffs are more culturally sensitive and more appreciating disability as part of cultural diversity. This research replicated the research reported by Sakiz and Woods [15] that the school staffs in Turkey hold positive beliefs in the disability inclusion. The positive response of staff in cultural dimension of disability inclusion shows a promising inclusive practice since staffs provide services and supports the facilities for the students.…”
Section: Discussionsupporting
confidence: 89%
“…This finding demonstrates that the academic staffs are more culturally sensitive and more appreciating disability as part of cultural diversity. This research replicated the research reported by Sakiz and Woods [15] that the school staffs in Turkey hold positive beliefs in the disability inclusion. The positive response of staff in cultural dimension of disability inclusion shows a promising inclusive practice since staffs provide services and supports the facilities for the students.…”
Section: Discussionsupporting
confidence: 89%
“…Hospitals provide a report that notes the presence or absence of the condition but it does not specify the subtype of LD, (i.e., reading difficulty (dyslexia), writing difficulty (dysgraphia), and/or difficulty in mathematics (dyscalculia)). On the other hand, GRCs, which are supervised by the Ministry of Education, carry out educational identification of LD by using IQ assessment and measuring academic performance of children in reading, writing, and mathematics and (Sakız & Woods, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of those studies, some reported that teachers hold positive attitudes towards inclusion of children with special needs (Avramidis, Bayliss, and Burden 2000;Hadjikakou and Mnasonos 2012;Park and Chitiyo 2011;Sakiz and Woods 2014;Sari 2007;Sucuoglu 2004), while some others showed that teachers possess negative (Alquraini 2012;Block and Obrusnikova 2007;Gok and ErbaS 2011;Martin, Johnson, Ireland, and Claxton 2003;Mukhopadhyay 2014;Rakap and Kaczmarek 2010;Sadioglu et al 2013;Secer 2010;Semmel et al 1991) or neutral attitudes (Engstrand and Roll-Pettersson 2012;Leyser and Tappendorf 2001;Ross-Hill 2009;Sari, Celikoz, and Secer 2009) towards inclusion of children with disabilities. In their review of the literature, Avramidis and Norwich (2002) identified several factors that influence teachers' attitudes towards inclusion/integration.…”
Section: Literature On In-service and Pre-service Teacher Attitudes Tmentioning
confidence: 95%